Ralstonia solanacearum type III effector RipAA targets chloroplastic AtpB to modulate an incompatible interaction on Nicotiana benthamiana - Miao, Yangchen; Wu, Leilei; Xue, Qi; Zhang, Qiuyan; Zou, Huasong (Frontiers in Microbiology, 2023)
Introduction The type III effector RipAA of Ralstonia solanacearum GMI1000 plays a critical role in the incompatible interaction on Nicotiana benthamiana. Methods The RipAA was transiently expressed in N. benthamiana by Agrobacterium-mediated transformation. Chemical staining with trypan blue and DAB were conducted to examine the cell death and the accumulation of hydrogen peroxide (H2O2), respectively. The expression of the marker genes for salicylic acid (SA) and jasmonic acid (JA) signaling was evaluated by quantitative reverse transcription PCR (qRT-PCR). The proteins interacted with RipAA was identified from N. benthamiana by yeast two-hybrid and pull-down assays. A TRV-mediated gene silencing was used to assess the role of host gene in response to RipAA expression and R. solanacearum infection. Results and discussion RipAA induced the accumulation of hydrogen peroxide (H2O2) and genome DNA degradation in N. benthamiana, which were accompanied by a hypersensitive reaction. Simultaneously, the marker genes for salicylic acid (SA) signaling were induced and those for jasmonic acid (JA) signaling were reduced. N. benthamiana chloroplastic AtpB, the ATPase β subunit, was identified as an interactor with RipAA. The silencing of atpB in N. benthamiana resulted in the inability of RipAA to induce a hypersensitive response, a compatible interaction with GMI1000, and an enhanced sensitivity to bacterial wilt. Our data support the concept that RipAA determines host-range specificity by targeting the host chloroplastic AtpB.